Effect of Resource Distribution on Service Delivery of Public Water Service Providers in Kenya - Wamalwa, Martin; Atandi, Fred; Owino, Moses (European Journal of Business and Strategic Management, 2025)
Purpose: This study aimed to evaluate the influence of strategic partnership on service delivery among the public water service providers in Kenya. Methodology: The study employed a mixed-methods research design, specifically an explanatory sequential approach, to gain a comprehensive understanding of the research problem. This involved collecting and analyzing quantitative data first using a cross-sectional survey with structured questionnaires administered to a sample of personnel within public water service providers in Kenya. This quantitative phase aimed to test hypotheses and establish relationships between variables. Following this, a qualitative phase was conducted using semi-structured interviews with key stakeholders, such as managers and staff, to provide in-depth insights and contextual explanations for the quantitative findings. This integrated approach allowed for both the testing of relationships and a deeper exploration of the underlying factors influencing service delivery. The target population for the study comprised all 88 public water service providers in Kenya, focusing on key management and staff members involved in service delivery, totaling 352 potential respondents. To ensure a manageable yet representative sample, the study utilized the Krejcie and Morgan formula, which yielded a sample size of 184 respondents selected from 46 randomly chosen water service providers, stratified by size. The data collected through both quantitative and qualitative instruments were analyzed using descriptive statistics to summarize the data and inferential statistics, specifically regression analysis, to examine the relationships between strategic partnership, resource distribution, diversification, innovativeness, and service delivery, as guided by the study's hypotheses. Findings: The study achieved a high response rate of 76.63% from the distributed 184 questionnaires. Descriptive statistics for resource distribution showed generally high levels of agreement among respondents, with average mean scores around 3.96 on a 5-point scale (ranging from 3.87 to 4.06) and average standard deviations around 0.92 (ranging from 0.82 to 0.99), indicating a shared positive view on the importance of various resource distribution aspects for service delivery. Pearson correlation analysis revealed a strong positive correlation between human resource placement and service delivery (r = 0.832, p < 0.001), and between investment portfolios and service delivery (r = 0.812, p < 0.001), while the correlation between physical infrastructure and service delivery was not statistically significant (r = 0.040, p = 0.664). The multiple regression model demonstrated a strong overall relationship between resource distribution and service delivery, with an R-squared value of 0.860 (adjusted R-squared = 0.856), and the ANOVA indicated the model was statistically significant (F(3,116) = 237.006, p < 0.001). The regression coefficients showed that human resource placement (β = 0.576, p < 0.001) and investment portfolios (β = 0.512, p < 0.001) had a significant positive effect on service delivery, while physical infrastructure did not (β = -0.037, p = 0.273). Unique Contributions to Theory, Practice and Policy: Based on the findings, this study uniquely contributes to theory, policy, and practice by demonstrating the critical role of strategic resource distribution, particularly in human resources and technology investments, in enhancing service delivery within the public water sector in Kenya. The findings support the Stakeholder Theory by highlighting how engagement informs resource allocation strategies. For policy, the study underscores the need for an enabling regulatory framework that facilitates digital transformation and ensures financial sustainability to support these crucial investments. In practice, the study recommends that public water service providers prioritize strategic human resource placement and development, along with investments in business technology portfolios, and strengthen partnerships to optimize resource utilization and improve service delivery outcomes.